Surrogate decision-maker for end-of-life care in terminally ill patients at Chiang Mai University Hospital, Thailand - Sittisombut S. (2014)
Surrogate decision-maker for end-of-life care is indicated at certain points during care for patients with terminal illnesses. This study aimed at identifying person(s) to whom northern Thai patients with terminal illnesses wished to transfer their decisions on end-of-life care and for cardiopulmonary resuscitation. From interviews with 152 eligible subjects, 57.2% had a high regard for their physicians' authority in making decisions on end-of-life care, 28.3% transferred their decisions to relative(s) and only 14.5% opted for shared decision-making among relative(s) and physicians. In the provision of cardiopulmonary resuscitation, 44.1% of subjects expressed a desire for family to make decisions together with physicians, 33.6% gave directives to the family alone and only 22.4% transferred their decisions to physicians. The differences that were observed in patients' preferences between the two situations indicate that patients should be assessed individually and adequate information for decision-making should be provided. © 2009 Blackwell Publishing Asia Pty Ltd.